2023
DOI: 10.1590/1807-1929/agriambi.v27n4p287-292
|View full text |Cite
|
Sign up to set email alerts
|

Pre-slaughter management in Northeast Brazil and the effects on thermophysiological indicators in pigs and pH45

Abstract: Inadequate pre-slaughter handling practices may compromise animal welfare and pork quality. This study aimed to evaluate the effects of transport period (TT), unloading period (UT), and pre-slaughtering period (WT) on animal thermophysiological indicators and pork pH using a multivariate approach. This study was conducted in a slaughterhouse located in Aquiraz, Ceará state, Brazil. A total of 60 mestizo pigs with 107 ± 5 kg body weight were distributed into three experimental groups: group A (TT = 180 min, UT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In this experiment, transport processes caused a negative impact on the incidence of skin injury in pigs, which has also been observed in other studies in Brazil (Dalla Costa et al, 2007a;Dalla Costa, 2017, Melo et al, 2023. In addition to reports in literature on the negative effect of greater distances of transport on mortality rate, live weight yield, animal welfare (Gosálvez et al, 2006;Barton Gade, 2008b, 2008a and between greater transport duration and injuries (Mota-Rojas et al, 2006;Sutherland et al, 2009), in this experiment, higher increase proportions of elevated scores (3 and 4) were not linear according to distance and duration (Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…In this experiment, transport processes caused a negative impact on the incidence of skin injury in pigs, which has also been observed in other studies in Brazil (Dalla Costa et al, 2007a;Dalla Costa, 2017, Melo et al, 2023. In addition to reports in literature on the negative effect of greater distances of transport on mortality rate, live weight yield, animal welfare (Gosálvez et al, 2006;Barton Gade, 2008b, 2008a and between greater transport duration and injuries (Mota-Rojas et al, 2006;Sutherland et al, 2009), in this experiment, higher increase proportions of elevated scores (3 and 4) were not linear according to distance and duration (Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…In conclusion, the frequency of PSE pork was low in the order of NT, LT, and HT, whereas the frequency of RFN pork was high. Previous studies have also reported that an increase of air temperature can lead to higher incidence of PSE pork [ 64 67 ]. These results show that the probability of PSE pork occurrence is the lowest when pigs are transported at a TCZ temperature and that heat stress can increase the probability of PSE pork occurrence compared to cold stress.…”
Section: Resultsmentioning
confidence: 98%